2018
DOI: 10.1002/ejic.201800371
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of Triple‐Decker Sandwich Complexes Containing Four‐Membered Open B2E2 Rings (E = S or Se)

Abstract: Building upon our earlier studies of cobaltaheteroboranes, we explore the chemistry with heavier group 9 metals. Reaction of [Cp*M(μ-Cl)Cl x ] 2 (Cp* = η 5 -C 5 Me 5 ; M = Co, x = 0; M = Rh or Ir, x = 1) with [LiBH 4 ·THF], followed by thermolysis with an excess of chalcogen powders (S or Se), affords dimetallaheteroboranes nido-[(Cp*M) 2 B 2 H 2 E 2 ], 1-4 (1: E = S; 2: E = Se, M = Co; 3 and 4: E = Se, M = Rh and Ir, respectively) in moderate-to-good yields. The solid-state structures of these compounds show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 94 publications
1
7
0
1
Order By: Relevance
“…As shown in Figure c, X-ray analysis revealed 6 as the diselenorhodaborane analogue of nido - 3 – 5 . The average B–B, Rh–Se, and Rh–B bond distances of 6 of 1.81, 2.42, and 2.20 Å, respectively, are comparable with the reported related rhodaheteroboranes. , …”
supporting
confidence: 84%
See 1 more Smart Citation
“…As shown in Figure c, X-ray analysis revealed 6 as the diselenorhodaborane analogue of nido - 3 – 5 . The average B–B, Rh–Se, and Rh–B bond distances of 6 of 1.81, 2.42, and 2.20 Å, respectively, are comparable with the reported related rhodaheteroboranes. , …”
supporting
confidence: 84%
“…The average B−B, Rh−Se, and Rh−B bond distances of 6 of 1.81, 2.42, and 2.20 Å, respectively, are comparable with the reported related rhodaheteroboranes. 17,18 When the molecular orbitals of the Cp analogues of nido-3− 5 were compared, it was observed that the highest occupied molecular orbital (HOMO)−lowest unoccupied molecular orbital (LUMO) energy gap decreased when the chalcogen atom was changed from S to Te (Table S1). On the other hand, when the metal was changed from Co to Rh, the HOMO−LUMO energy gap increased (Table S1).…”
mentioning
confidence: 99%
“…These bond distances are somewhat longer in comparison to a bimetallic species having a similar core, [(Cp*M) 2 B 2 H 2 Se 2 ] (M = Rh, Ir). 21 Note that there are no noticeable intermolecular atom− atom contacts in the crystal phases of both 1 and 2, apart from a weak Se•••H interaction between Cp* and the Se atom (average…”
mentioning
confidence: 79%
“…The reactions indeed led to the formation of heterotrimetallalic complexes, [(Cp*MB 2 H 3 Se 2 ) 2 (μ 4 -Zn)] ( 1 , M = Ir; 2 , M = Rh) comprising a tetrahedral ZnSe 4 fragment along with [(Cp*M) 2 B 2 H 2 Se 2 ] (M = Ir, Rh) complexes (Scheme ). [(Cp*IrB 2 H 3 Se 2 ) 2 (μ 4 -Zn)] ( 1 ) was isolated as a yellow solid in 31% yield, while (Cp*RhB 2 H 3 Se 2 ) 2 (μ 4 -Zn)] ( 2 ) was obtained as a red solid in 4% yield . A comparison of their spectroscopic data first indicated the analogous nature of 1 and 2 .…”
mentioning
confidence: 99%
See 1 more Smart Citation